2010
DOI: 10.1021/la1028959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Encapsulated Bubble in Inhibiting Droplet Sliding

Abstract: The transport of liquid droplets on surfaces carrying reactants offers advantages in the creation of fluidic devices crucial for life science applications. In a majority of situations, a selection of these droplets on a surface, rather than all of them, will need to be moved at any one time. It is a formidable challenge to deliver the motive energy source only to specific droplets while leaving the others unmoved. Here, we describe an alternative novel solution of momentarily pinning specific droplets to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…For example, when a bubble was introduced on a superaerophilic interface with a constant curvature rather than a smooth one, the gas bubbles stay on it as a spherical crown shape even though the gas bubble dia meter is small. [59,60] The smaller the interface curvature, the smaller the diameter of spherical crown-shaped gas-bubble is captured. [44] Cu 3 P microsheets (lateral size: 6 µm, thickness: 510 nm) [46] Amorphous MoS 2 porous thin film constructed by nanosheets with the size of several micrometers [50] Pine-shaped Pt nanoarray [27] HzOR Vertically aligned Cu nanoplate array (average size: 500 nm, thickness: 50 nm) [31] Ultrathin Ni nanosheet arrays (2.2 nm) [44] Ni nanoflower electrodes [45] 3D porous Ni-Cu alloy film (400 nm flower-like nanostructure) [51] ClER RuO 2 @TiO 2 nanosheet array (irregular sheet-like units with lateral size 200 nm and thickness 20 nm) [47] OER Cu 3 P microsheets (lateral size 6 µm; thickness 510 nm) [46] NiFe-LDH nanoplates (500 nm) vertically grown on Ni foam [48] Zn x Co 3−x O 4 nanostructures constructed with secondary nanoneedles grown on primary rhombus-shaped pillar arrays (pillar length 15 µm) [52] Core-shell-structured Ni 2 Co 1 @Ni 2 Co 1 O x powder (nanoparticle diameters over 50 nm) [53] observations and scanning electron microscope (SEM) images of thicker, porous, skeleton structures on superaerophilic sponge.…”
Section: Directional Gas-bubble Transport On Superaerophilic Copper-wmentioning
confidence: 99%
“…For example, when a bubble was introduced on a superaerophilic interface with a constant curvature rather than a smooth one, the gas bubbles stay on it as a spherical crown shape even though the gas bubble dia meter is small. [59,60] The smaller the interface curvature, the smaller the diameter of spherical crown-shaped gas-bubble is captured. [44] Cu 3 P microsheets (lateral size: 6 µm, thickness: 510 nm) [46] Amorphous MoS 2 porous thin film constructed by nanosheets with the size of several micrometers [50] Pine-shaped Pt nanoarray [27] HzOR Vertically aligned Cu nanoplate array (average size: 500 nm, thickness: 50 nm) [31] Ultrathin Ni nanosheet arrays (2.2 nm) [44] Ni nanoflower electrodes [45] 3D porous Ni-Cu alloy film (400 nm flower-like nanostructure) [51] ClER RuO 2 @TiO 2 nanosheet array (irregular sheet-like units with lateral size 200 nm and thickness 20 nm) [47] OER Cu 3 P microsheets (lateral size 6 µm; thickness 510 nm) [46] NiFe-LDH nanoplates (500 nm) vertically grown on Ni foam [48] Zn x Co 3−x O 4 nanostructures constructed with secondary nanoneedles grown on primary rhombus-shaped pillar arrays (pillar length 15 µm) [52] Core-shell-structured Ni 2 Co 1 @Ni 2 Co 1 O x powder (nanoparticle diameters over 50 nm) [53] observations and scanning electron microscope (SEM) images of thicker, porous, skeleton structures on superaerophilic sponge.…”
Section: Directional Gas-bubble Transport On Superaerophilic Copper-wmentioning
confidence: 99%
“…What is also noteworthy is the advancing contact angle even being generally smaller than the equilibrium contact angle. This seemingly anomalous behavior with the contact angle can be explained by the ability of the drop to breach its front contact line first [17,18]. With the back contact line still pinned to the surface, the drop is able to undergo a transient elongation.…”
Section: Resultsmentioning
confidence: 99%
“…Plastrons are also believed to be responsible for the ability of sessile bubbles to exist on the SH surfaces at volumes much larger than anticipated [24]. On non-SH PTFE, it is conceivable that regions of non-visible surface air entrapment may continue to exist even when the larger bubbles dissipate through diffusion [17]. In aqueous solutions, glycerol is well known to be able to disrupt the hydrogen-bonded structure of water, thereby making the solution more compact [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for surfaces with a receding contact angle greater than 90°, such as those with low contact angle hysteresis, this is unlikely to occur for bubbles in the micron size range. A recent study has identified how the interaction between a bubble (with a size comparable to the drop size) and the liquid interface deforms the interface and results in additional pinning [35]. The rupture of such a bubble causes the immediate unpinning of a drop.…”
Section: Interaction Between Bubbles and The Contact Linementioning
confidence: 99%